Pengaruh atribusi kemiskinan, keadilan dunia dan gaya pembuatan keputusan terhadap kesejahteraan psikologi dalam kalangan kumpulan B40 di Malaysia - Rozmi Ismail,; Nurfatin Akila Jeli, (Penerbit Universiti Kebangsaan Malaysia, 2020)
This study examines how attribution towards poverty, just world belief and decision-making styles contribute to the psychological well-being of the low-income group or known as B40 in Malaysia. The study predicted that attribution towards poverty, just-world belief and decision making style are related to how they define the causes of poverty and thus will affect their subjective wellbeing. There were 384 respondents of low income group from rural and sub-urban randomly selected and participated in this survey. The findings showed that B40 group in Malaysia perceived poverty as attributed to micro-environmental (eq. living in poverty and unable to feed family members) and fatalistic factors (eq. had illness). The study also found that perception towards belief in Just-world was the best predictor for subjective wellbeing. As for the decision-making style, majority used rational decision making style and dependent style. The implication of this study suggested that perception towards the just-world phenomenon and poverty attribution contribute in shaping the negative mind-set of this group towards government agenda and thus impacting their subjective well-being.